The latitudinal gradient of functional diversity of Miocene marine mollusks from Chile. Issue 2 (20th December 2022) - Grossmann, Mariana; Nielsen, Sven N.; Rivadeneira, Marcelo M.; Valdivia, Nelson
Abstract : Understanding latitudinal variations in biodiversity is central for biogeography. Along the coasts of the Southeast Pacific, several taxa show inverse latitudinal patterns of biodiversity, i.e. increasing species numbers from lower to higher latitudes. A plausible explanation for these patterns is that fjords, formed during the Pleistocene glaciations, increased the diversity of available biotopes that allowed for higher diversity in high latitudes. Assessing this hypothesis requires us to analyze latitudinal patterns of functional diversity (which is intimately related to niche use) in the absence of fjords, i.e. earlier than their formation. Here we test if the fossil record before the generation of fjords shows higher functional diversity at lower than at higher latitudes (a 'regular' functional diversity gradient). We analyzed four components of functional diversity (functional richness, functional divergence, functional dispersion and functional evenness) for a fossil marine mollusk fauna from the lower Miocene ( 18 million years ago) across four regions spanning more than 10 latitudinal degrees of the Chilean coast (between 34°S and 45°S). The functional richness of gastropods and bivalves decreased non‐linearly from low to high latitudes. Contrarily, the functional evenness of gastropods remained relatively constant across the region and that of bivalves peaked at 45°S. The functional divergence and functional dispersion of taxonomic groups did not exhibit clear patterns of latitudinal variation. The multivariate analysis uncovered non‐linear latitudinal patterns in the abundance of functional groups (gastropods and bivalves), with the largest abundance towards lower latitudes. These results suggest that the niche breadth of mollusk assemblages might have decreased with latitude in the lower Miocene. This work can shed light on the mechanisms underlying the latitudinal variation of diversity observed today, offering a better understanding of how these patterns changed over time.